2000
DOI: 10.1017/s0950268899004161
|View full text |Cite
|
Sign up to set email alerts
|

The sero-epidemiology of diphtheria in Western Europe

Abstract: Seven countries in Western Europe collected large, representative serum banks across the entire age range and tested them for diphtheria anti-toxin (sample size ranged from 2991 to 7715). Although a variety of assays were used, the results were all standardized to those of a reference laboratory and expressed in international units. The standardization process, and the availability of similar, large data sets allowed comparative analyses to be performed in which a high degree of confidence could be ascribed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 34 publications
12
80
2
1
Order By: Relevance
“…They also correlate with data from different studies showing that many American and European subjects over 50 years old do not have sera protective concentrations of anti-DT antibodies. [14][15][16] Despite the fact that a second booster was not recommended in France before 1998, we observed that 74% of the subjects had received more than one pertussis booster. Anti-PT antibody of ≥125 IU/mL suggesting a very recent infection were found in 7.6% of the study population, and this percentage was higher (13.4%) in those aged 18-29 years (mean age, 23 years; 95% CI, 21.27-24.75).…”
Section: Resultsmentioning
confidence: 68%
“…They also correlate with data from different studies showing that many American and European subjects over 50 years old do not have sera protective concentrations of anti-DT antibodies. [14][15][16] Despite the fact that a second booster was not recommended in France before 1998, we observed that 74% of the subjects had received more than one pertussis booster. Anti-PT antibody of ≥125 IU/mL suggesting a very recent infection were found in 7.6% of the study population, and this percentage was higher (13.4%) in those aged 18-29 years (mean age, 23 years; 95% CI, 21.27-24.75).…”
Section: Resultsmentioning
confidence: 68%
“…Details of the sources of sera and methods of collection have been described previously [27]. A minimum number of sera to be collected in each age group was established, with equal numbers by gender in each age group.…”
Section: Serum Survey Collectionmentioning
confidence: 99%
“…The sources of sera used have been described previously [8]. Two methods of sampling were used : population based random sampling and use of residual sera collected during routine laboratory testing.…”
Section: Serum Survey Collectionmentioning
confidence: 99%